2012
DOI: 10.1021/es2033845
|View full text |Cite
|
Sign up to set email alerts
|

Are Emissions of Black Carbon from Gasoline Vehicles Underestimated? Insights from Near and On-Road Measurements

Abstract: Measurements of black carbon (BC) with a highsensitivity laser-induced incandescence (HS-LII) instrument and a single particle soot photometer (SP2) were conducted upwind, downwind, and while driving on a highway dominated by gasoline vehicles. The results are used with concurrent CO 2 measurements to derive fuel-based BC emission factors for real-world average fleet and heavy-duty diesel vehicles separately. The derived emission factors from both instruments are compared, and a low SP2 bias (relative to the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
5
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 67 publications
6
78
5
2
Order By: Relevance
“…This is true even though the vehicles sampled in the on-road and tunnel studies typically do not operate under cold-start conditions and therefore should, in principle, emit less BC. Our EFBC's are, in particular, much lower than the median values reported in Park et al 31 and Liggio et al 32 The average EFBC here is 5.2 mg kg This is likely due to implementation of improved emission control technologies in newer vehicles, allowing for more ideal fuel-to-air ratios. Thus, the oldest vehicles sampled in the on-road studies (with median vehicle ages of ~10 years) 33 likely push the average EFBC upwards.…”
Section: Comparison With On-road and Tunnel Studiescontrasting
confidence: 76%
See 1 more Smart Citation
“…This is true even though the vehicles sampled in the on-road and tunnel studies typically do not operate under cold-start conditions and therefore should, in principle, emit less BC. Our EFBC's are, in particular, much lower than the median values reported in Park et al 31 and Liggio et al 32 The average EFBC here is 5.2 mg kg This is likely due to implementation of improved emission control technologies in newer vehicles, allowing for more ideal fuel-to-air ratios. Thus, the oldest vehicles sampled in the on-road studies (with median vehicle ages of ~10 years) 33 likely push the average EFBC upwards.…”
Section: Comparison With On-road and Tunnel Studiescontrasting
confidence: 76%
“…It seems unlikely that there would be enough malfunctioning vehicles on the road to substantially influence the median (especially for studies conducted in locations that require periodic vehicle emissions testing, such as California). Additionally, studies that report both the mean and the median 31,32 indicate that the mean is only around 2-3 times higher than the median.…”
Section: Comparison With On-road and Tunnel Studiesmentioning
confidence: 99%
“…Wang et al [33] and Huang et al [34] find a larger secondary mode in rural areas of Qinghai Lake (mass median diameter, MMD: 495 nm) and Kaiping (MMD: 690 nm), China, where biofuel/biomass burning are the main sources for rBC. Previous studies have shown that rBC particles from biomass burning tend to be rather large [35], while motor vehicles generally emit smaller rBC particles [36,37]. Thus, the small secondary size mode in Xi'an may be the result of vehicular emissions.…”
Section: Rbc Mass Size and Mixing Statementioning
confidence: 96%
“…This rough estimate for a minimum GMD was chosen, because the agglomeration in BC formation produces a roughly lognormal mode and we assumed that it would not form particles in the smallest size ranges of the modes with GMD below 50 nm (Sorensen and Feke, 1996;Kholghy et al, 2013). This assumption seems reasonable for diesel-fuelled vehicles, but might not be valid for gasoline-fuelled vehicles (Liggio et al, 2012). However, as the global emissions from diesel-fuelled vehicles are found to dominate the transport emissions, we will leave the further improvements on defining the black carbon modes to future studies.…”
Section: Black Carbon Size Distribution Estimatesmentioning
confidence: 99%
“…2.3, and some of the sub-50 nm particles here defined as non-BC particles might in reality have a BC core. Even though this possible underestimation of smaller BC particles is unlikely to concern the diesel emissions (Liggio et al, 2012), which is the main source for BC number emissions, the black carbon Figure 8. Shares of different source sectors to the future global trends in particle number and mass emissions under current legislation scenario: PN emissions in ultrafine and fine size ranges and particle mass emissions PM 1 , PM 2.5 and black carbon.…”
Section: Black Carbon Emission Size Distributionmentioning
confidence: 99%